Synthesis of Nb/MCM-48 material using rice husk ash as silica source with different SI/NB molar ratios (Revista Perspectiva, 2021)
The large amount of rice produced in Brazil generates a large volume of co-products, such as, Rice Husk (RH) and Rice Husk Ash (RHA). These co-products have amounts of silicon (Si) present in their structure, which can be used to synthesize silica-based materials as zeolites and MCM-type structures. The synthesis of MCM-48 material was carried out at room temperature, using the ionic liquid [C16MI·Cl] as structure-directing agent, depositing the niobium in situ during the synthesis with different molar ratios of Si/Nb (5, 20, 50 and 80). The material obtained was subjected to characterization by X-Ray Diffraction (XRD), Nitrogen Adsorption/Desorption isotherms and Scanning Electron Microscopy (SEM). The results confirm the formation of Nb/MCM-48 materials, in which their properties are consistent with those described in the literature. The deposition of Nb on MCM-48 did not change its structural properties, such as specific surface area and pore distribution for Si/Nb higher than 5. The results obtained demonstrate the success in the synthesis of mesoporous materials Nb/MCM-48 using industrial residues of rice as an alternative source of silicon, and in situ deposition of the niobium metal on the structure.
Keywords: One-Pot synthesis; MCM-48; Silicon; RHA; Niobium